Implementasi Supervisi Pimpinan dalam Upaya Meningkatkan Kualitas Kinerja Pegawai Negeri Sipil (PNS) pada Bagian Perekonomian di Sekretariat Daerah Kabupaten Langkat - Tengku Natasya Febriani; Novita Sari; Muhammad Saleh (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study aims to analyze the implementation of leadership supervision in efforts to improve the performance quality of Civil Servants (PNS) in the Economic Affairs Section at the Regional Secretariat of Langkat Regency. The research findings indicate that the effectiveness of supervision greatly depends on clear objectives, performance indicators, periodic evaluations, and open communication between leaders and staff. Although there are challenges such as ineffective communication and imbalanced workloads, proposed solutions include improving communication and utilizing technology to enhance supervision and employee performance. Optimal supervision has been shown to play a key role in improving PNS performance, with an emphasis on monitoring, evaluation, and skill development. Despite challenges like limited resources and ineffective communication, solutions such as training, open communication, and technology can improve supervision efficiency. Most PNS show a positive attitude towards management and supervision, although there is still room for improvement in communication and skill development. Going forward, it is expected that supervision will become more structured, technology-based, and communicative to support the achievement of organizational goals more efficiently and enhance public service quality.